Redox-active guanidine ligands with pyridine and p-benzoquinone backbones - Stang, Simone; Lebkücher, Anna; Walter, Petra; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2012)
Herein we report on the synthesis and some aspects of the chemistry of the new redox-active ligands 2,3,5,6-tetrakis(tetramethylguanidino)pyridine, 2,3,5,6-tetrakis(tetramethylguanidino)-p-benzoquinone and 2,3,5,6-tetrakis(N,N′-dimethyl-N,N′-ethyleneguanidino)-p-benzoquinone. All three ligands are strong electron donors. In addition, the p-benzoquinone systems feature low LUMO energies and small HOMO-LUMO gaps. A comparison of the ligands was made with regard to their optical properties, Brønsted basicity and electron-donor properties; results of quantum chemical calculations were included in this comparison. Subsequently, dinuclear copper complexes were prepared. Preliminary experiments on their redox chemistry followed.